2020
DOI: 10.3389/fpls.2020.00823
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characteristics of Two Molecular Variants of the Nitrogen Sensor PII in Maritime Pine

Abstract: High levels of nitrogen are stored as arginine during the last stages of seed formation in maritime pine (Pinus pinaster Aiton). The protein sensor PII regulates the feedback inhibition of arginine biosynthesis through interaction with the key enzyme N-acetylglutamate kinase (NAGK). In this study, the structural and functional characteristics of PII have been investigated in maritime pine to get insights into the regulation of arginine metabolism. Two different forms of PII have been identified, PpPIIa and PpP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In Arabidopsis cells, PII was detected for the first time in chloroplasts by immunolocalization in a dotted pattern [ 35 ]. GFP fusions of two PII isoforms from maritime pine ( Pinus pinaster ) expressed in tobacco cells also revealed a similar localization pattern [ 36 ]. Focal aggregation of PII has even been observed in evolutionary distant organisms such as the cyanobacterium Synechococcus elongatus [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis cells, PII was detected for the first time in chloroplasts by immunolocalization in a dotted pattern [ 35 ]. GFP fusions of two PII isoforms from maritime pine ( Pinus pinaster ) expressed in tobacco cells also revealed a similar localization pattern [ 36 ]. Focal aggregation of PII has even been observed in evolutionary distant organisms such as the cyanobacterium Synechococcus elongatus [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Revisiting former localization studies of plant PII proteins revealed that the aggregation of this protein in plastids had been indeed observed before, but did not attract further interest: In Arabidopsis cells PII was detected for the first time in chloroplasts by immunolocalization in a dotted pattern [35]. GFP fusions of two PII isoforms from maritime pine (Pinus pinaster) expressed in tobacco cells also revealed a similar localization pattern [36]. Focal aggregation of PII has even been observed in distant organisms like the cyanobacterium Synechococcus elongatus [37].…”
Section: Discussionmentioning
confidence: 94%
“…However, when high levels of nitrogen (N) are available, the protein sensor PII interacts with NAGK to relieve this feedback control, increasing the metabolic flux through the pathway for N storage ( Llaìcer et al, 2008 ). Two isoproteins of PII, PIIa, and PIIb, have been described in maritime pine, with PIIa being the predominant form in developing embryos ( Llebrés et al, 2020 ). Compared to zygotic embryos, the enhanced expression of ASS and ARG genes in somatic embryos ( Figure 7 ) is consistent with the simultaneous synthesis and degradation of arginine, as previously suggested ( Pérez-Rodríguez et al, 2006 ; Llebrés et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%